Cyber warfare: a study of Zelenskyy’s social media political performance strategies and effects - Wang, Liqiang; Wang, Ruonan (Frontiers in Psychology, 2024)
During the Russia-Ukraine war, Ukrainian President Volodymyr Zelenskyy has strategically used social media to appeal for international support. This reflects a broader trend of political figures relying on digital platforms to shape public opinion and influence global narratives during crises.Based on theories of dramaturgy, framing, and network agenda-setting, this study explores the impact of his political performance strategies within the context of the ongoing conflict. Through the Twitter Academic API, 604 valid tweets and 58,100 corresponding comments are collected. And then we comprehensively use content analysis, sentiment analysis and social network analysis to conduct a quantitative analysis of Zelenskyy's wartime social media narrative, performance and effect. The findings show that Zelenskyy employs both textual and visual narratives to construct a war-related agenda, influencing international public discourse. His agenda-setting is most effective in the early stages of the conflict but weakens over time. This study highlights Zelenskyy's flexibility and adaptability in his media strategy, illustrating the evolving nature of political performance in a globalized media landscape. To maintain effective communication and image-building, leaders must balance audience psychology with the characteristics of digital media.